2014
DOI: 10.1128/jvi.01745-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mode of Action of a Potent Dengue Virus Capsid Inhibitor

Abstract: Dengue viruses (DV) represent a significant global health burden, with up to 400 million infections every year and around 500,000 infected individuals developing life-threatening disease. In spite of attempts to develop vaccine candidates and antiviral drugs, there is a lack of approved therapeutics for the treatment of DV infection. We have previously reported the identification of ST-148, a small-molecule inhibitor exhibiting broad and potent antiviral activity against DV in vitro and in vivo (C. M. Byrd et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 67 publications
2
64
0
Order By: Relevance
“…This genetic complementation results in the production of pseudoinfectious virus-like particles capable of only a single round of infection, referred to herein as reporter virus particles (RVPs). RVPs have been used extensively to study flavivirus biology (43)(44)(45)(46)(47)(48) and virus-antibody interactions (35,36,(49)(50)(51) and as tools to screen antiviral compounds (19,52,53). The mechanism of flavivirus RNA packaging is not well understood and appears to be relatively nonselective.…”
Section: Resultsmentioning
confidence: 99%
“…This genetic complementation results in the production of pseudoinfectious virus-like particles capable of only a single round of infection, referred to herein as reporter virus particles (RVPs). RVPs have been used extensively to study flavivirus biology (43)(44)(45)(46)(47)(48) and virus-antibody interactions (35,36,(49)(50)(51) and as tools to screen antiviral compounds (19,52,53). The mechanism of flavivirus RNA packaging is not well understood and appears to be relatively nonselective.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, investigation on the mode of FCV inhibition by fexaramine by various experiments including the time-of-addition studies and analysis of viral resistance showed that, in contrast with inhibition of rotavirus , fexaramine acts as an entry inhibitor of FCV. Virus entry inhibitors have been developed or reported for enveloped viruses including human immunodeficiency virus (HIV) (Haqqani and Tilton, 2013;Woollard and Kanmogne, 2015), influenza virus (Palese and Shaw, 2007), Measles virus (Plemper et al, 2005) and Dengue virus (Scaturro et al, 2014). Virus entry inhibitors have also been reported for non-enveloped viruses including picornaviruses including poliovirus (Thys et al, 2008), enterovirus (Buontempo et al, 1997;Ho et al, 2016;Ma et al, 2017;Torres-Torres et al, 2015) and rhinoviruses Kim et al, 2017;Tijsma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A recent high-throughput screen identified a small molecule (ST-148) that potently inhibits replication of all four DENV serotypes in vitro by targeting the capsid protein (130). ST-148 has been proposed to enhance capsid self-interaction, likely perturbing viral assembly and disassembly (91). Interestingly, despite the presence of viral variants with resistance to ST-148 in the population, selection for resistant viruses was not observed (131).…”
Section: Capsid Protein and Antiviral Strategiesmentioning
confidence: 99%